Factors Affecting the Implementation of the Internal Control System: Control Environment, Risk Assessment and Control Activities - Riza, M. Difa; Kuntadi, Cris (PT.KARYA GEMAH RIPAH, 2024)
Weaknesses in the internal control system need serious attention because their implementation is not optimal, especially in government agencies that often face internal control problems. This study focuses on finding evidence from the literature related to the factors that influence internal control system weaknesses through the components of the Control Environment, Risk Assessment, and Control Activities. This study uses a qualitative approach and library research method, by examining the relationship of theories and elements collected from books, journals, and online sources such as Mendeley, Google Scholar, and various other online media. The results showed that the positive effect of the control environment on auditor accountability in the implementation of the internal control system, risk assessment has a positive effect on auditor accountability but is not significant on financial statement accountability, effective control activities, such as separation of duties and adequate documentation, are important to improve accountability and integrity in the management of the organization.